1992
DOI: 10.1128/iai.60.8.3446-3447.1992
|View full text |Cite
|
Sign up to set email alerts
|

Mouse neutrophils lack defensins

Abstract: Defensins are broad-spectrum antimicrobial peptides that are abundant in human, rat, and rabbit neutrophils. We now report that neutrophils from nine strains of mice lacked appreciable defensin content. Mice may therefore be imperfect experimental surrogates for humans or rats in models of infection in which neutrophil function is significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(85 citation statements)
references
References 13 publications
1
81
0
1
Order By: Relevance
“…A recent study demonstrated that LL-37 was capable of a dosedependent suppression of HIV reverse transcriptase activity [133]. This study also demonstrated that this function was retained by a 16 amino acid fragment of LL-37 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), with implications for production of smaller synthetic analogues. Thus, epithelial expression of LL-37 has been proposed to contribute to local protection against HIV-1 infection.…”
Section: Hiv-1mentioning
confidence: 73%
See 1 more Smart Citation
“…A recent study demonstrated that LL-37 was capable of a dosedependent suppression of HIV reverse transcriptase activity [133]. This study also demonstrated that this function was retained by a 16 amino acid fragment of LL-37 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), with implications for production of smaller synthetic analogues. Thus, epithelial expression of LL-37 has been proposed to contribute to local protection against HIV-1 infection.…”
Section: Hiv-1mentioning
confidence: 73%
“…In contrast, HD5 and 6 are expressed by Paneth cells of the small intestine [15,16] and epithelial cells of the female genital tract [12,17,18]. Interestingly, although mice express a large number of intestinal a-defensins (cryptdins) [19], in contrast to humans they do not express a-defensins in their neutrophils [20,21].…”
Section: A-defensinsmentioning
confidence: 99%
“…They are also expressed by monocytes, macrophages, and certain DCs, and a subset of β-defensins are only expressed in the male reproductive tract [26,28]. Although there are commonalities in expression patterns of defensins in humans and other species, one important difference relevant for experimental models of infectious disease is that mice lack myeloid α-defensins [29,30].…”
Section: Defensin Structure Expression and Physiologic Concentrationsmentioning
confidence: 99%
“…Human -defensin genes exist and are transcribed, but the human genes and transcripts contain a premature stop codon that aborts translation (8), unless the cells are induced to read through the stop codon (49). Curiously, whereas rat and human PMN contain multiple ␣-defensins, murine PMN contain none (15,40).Retrocyclins inactivate anthrax lethal toxin and kill B. anthracis bacilli in vitro (51), and they are more effective than HNP 1 to 3 in preventing B. anthracis spores from germinating and commencing vegetative growth (51). Based on these findings, we performed additional in vitro studies with retrocyclins and B. anthracis and tested their ability to protect mice challenged in vivo with B. anthracis spores.…”
mentioning
confidence: 99%
“…Human -defensin genes exist and are transcribed, but the human genes and transcripts contain a premature stop codon that aborts translation (8), unless the cells are induced to read through the stop codon (49). Curiously, whereas rat and human PMN contain multiple ␣-defensins, murine PMN contain none (15,40).…”
mentioning
confidence: 99%